The value of online seller reputation: evidence from a price comparison site - Thompson, Stephen; Haynes, Michelle (Wiley, 2015)
This paper examines the value of seller reputation for e-retailers trading via a price comparison site (PCS). E-markets are widely held to accommodate sellers of differing service quality, including some who behave opportunistically. The paper uses a sample of offers on up to 295 digital cameras traded on a leading PCS, over a 134-day period to estimate reputation’s price impact. User-generated reputation measures have a significant impact in the expected direction. However, their magnitude is small compared to variables capturing economy-wide reputation. The strength of the reputation signal increased non-monotonically with the number of reviews on which it was based.